IMPACT OF THE EXISTENCE OF THE BTS TOWER (BASE TRANSCEIVER STATION) IN JATIROTO DISTRICT, WONOGIRI REGENCY YEAR 2021 - Muh Husyain Rifai (Journal of Geography Science and Education, 2022)
Noviasari, Anggi. NIM. 1751100010. Impact of the Existence of BTS Tower (Base Transceiver Station) in Jatiroto District, Wonogiri Regency in 2021. Supervisor : Muh Husyain Rifai,S.Pd,M.Pd. and Ary Wijayanti, S.Pd, M.Pd. Essay. Geography Education Study Program, Faculty of Teacher Training and Education, University of Veterans Bangun Nusantara, Sukoharjo. 2021. This study aims to determine: (1) the distribution and affordability of the BTS tower signal (2) The impact of the existence of the BTS tower on the education of students at SMKN 1 Jatiroto (3) The impact of the existence of the BTS tower on the economic changes of the community around the BTS tower. The method used in this study is a qualitative descriptive method. This study describes/describes and finds out the impact of the existence of BTS towers on the education of students of SMKN 1 Jatiroto and the economic changes of the surrounding community. Data collection techniques used are through observation, questionnaires and documentation. The results of the study can be concluded that: (1) The distribution and coverage of the BTS Tower Tower signal in Jatiroto District is spread over three areas and there are five BTS Tower Towers. Each BTS Tower can reach a signal as far as 5km and this is also influenced by the topography of the surrounding area (2) The impact of the existence of a BTS tower on the education of students at SMKN 1 Jatiroto has a positive impact in the form of making it easier for students to access the internet, making it easier for students to learn. The negative impact is radiation from the BTS tower signal and anxiety about the collapse of the BTS tower. (3) The impact of the existence of the BTS Tower on the economic changes of the surrounding community is that it can increase economic income, such as increasing income for people who sell credit and make it easier to access the internet. The negative impact is the increasing number of people's needs to buy credit which results in an increase in public spending, radiation from BTS tower signals.